In the digital landscape: Can social media marketing activities boost brand loyalty in the Jordanian hospitality sector? - Muneer Alrwashdeh; Nesrin Almatarneh; Lu’ay Al-Mu’ani; Ayman Hindieh (Innovative Marketing)
Type of the article: Research Article Abstract Customer loyalty is a pressing priority and strategic imperative in the Jordanian hotel sector. With the rapid technological transformation in consumer behavior, social media marketing activities have emerged as a tool for engaging with hotel guests and building long-term relationships. This paper aims to explore the impact of Social Media Marketing activities (SMM activities) on brand loyalty through the mediating role of brand love and brand trust in the five-star hotel sector. The study adopted a quantitative design, employing a descriptive correlational approach to examine the relationship between study variables. Data were collected from June 1, 2024, to September 30, 2024, using a structured online questionnaire from guests of five-star hotels in Jordan, in Amman. A purposive sample was used to select hotel guests, using social media platforms for 280 respondents. The questionnaire was designed to measure the variables of the study. Statistical analysis was conducted using Smart PLS to test the hypotheses. The study results indicate a significant impact of social media marketing activities (β = 0.299, p < 0.001) on brand loyalty, as well as the mediating role of brand trust (β = 0.09, p < 0.001) and brand love (β = 0.18, p < 0.001) in mediating the relationship between marketing activities and customer loyalty. The results also revealed a positive relationship between social media marketing activities and brand loyalty in the hotel sector. The results also indicate that brand love and trust mediate the relationship between social media marketing activities and brand loyalty, enhancing brand loyalty in the hotel industry. AcknowledgmentThe authors would like to thank all the participants involved in this research work, and the authors are grateful to the Philadelphia University, Amman, Jordan for the financial support granted to cover the publication fee of this article.